1990
DOI: 10.1111/j.1365-2621.1990.tb05220.x
|View full text |Cite
|
Sign up to set email alerts
|

Twin‐Screw Extrusion Modification of a Corn Fiber and Corn Starch Extruded Blend

Abstract: Surface response modeling was used to characterize the effect of extrusion processing on the functional properties of corn fiber/corn starch formulations. Process parameters evaluated included screw speed (ZOO-500 rpm), temperature (90-150°C) and pH (3-11). Generally, the water holding capacity of starch increased with increasing extrusion temperature while the water holding capacity of the fiber decreased with increasing extrusion temperature. The foam stability decreased, while the residual moisture increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 4 publications
5
52
0
4
Order By: Relevance
“…Ding et al (2005) also stated that the WAI decreases with increasing temperature if dextrinization or starch melting prevails over the gelatinization phenomenon. Similar findings were reported in extrusion of corn fiber and corn starch blend (Artz et al, 1990). Singh et al (2007) observed decrease in WAI with the addition of pea grits in extrusion of rice.…”
Section: Effect Of Process Variables On Product Waisupporting
confidence: 76%
“…Ding et al (2005) also stated that the WAI decreases with increasing temperature if dextrinization or starch melting prevails over the gelatinization phenomenon. Similar findings were reported in extrusion of corn fiber and corn starch blend (Artz et al, 1990). Singh et al (2007) observed decrease in WAI with the addition of pea grits in extrusion of rice.…”
Section: Effect Of Process Variables On Product Waisupporting
confidence: 76%
“…The expansion ratio (ER) was expressed as the mean diameter of the pasta to that of the die orifice (Art et al, 1990;James and Nwabueze, 2013).…”
Section: Expansion Ratiomentioning
confidence: 99%
“…Conway [36], Artz et al [37] and Badrie and Mellows [38] reported similar observation, where they all agree that at high temperature and …”
Section: /22mentioning
confidence: 59%